Přechylování – the twilight of tradition or a temporary crisis? Women’s surnames in the Czech language - Korbut, Joanna (Papers in Linguistics, 2024)
This article focuses on the issue of feminine forms of surnames in the Czech language, including the current legal and cultural status of andronyms and the attitude to this phenomenon among Czech society. In Czech, female surnames are most often derived from the man’s names, mostly by the suffix -ová, which is added to basic names. For many years, these forms were created almost automatically – in accordance with the applicable law both Czech and foreign surnames were suffixed. Over the last dozen years or so there have appeared significant changes in this area. The problem of creating female surnames from the husband’s name aroused a heated debate, leading to a gradual revision of the regulations governing this issue. On the 1 January 2022, an amendment to the act on female surnames entered into force. According to the new law, Czech women are no longer obliged to use feminine suffixes in surnames – they can decide which form of the surname they want to use. It is impossible to determine today whether they will exercise this right, and whether the legal change will result in (as some linguists predict) significant changes in the grammatical system of the Czech language.